Streptomycin – Like Antibiotic from Streptomyces spp. Isolated from Mount Everest Base Camp - Yadav, Jyotish; Shrestha, Upendra Thapa; Tiwari, Kiran Babu; Sahukhal, Gyan Sundar; Agrawal, Vishwanath Prasad (Nepal Journal of Science and Technology, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Streptomyces spp. (Lob18.2b), isolated from soil sample from Everest Base Camp, was obtained from Research Laboratory for Biotechnology and Biochemistry (RLABB). The isolate was found to inhibit Salmonella paratyphi, Salmonella typhi, Proteus mirabilis, Proteus vulgaris, Shigella sonnei, Klebsiella pneumoniae, Klebsiella oxytoca, Escherichia coli, Bacillus subtilis and Staphylococcus aureus on primary screening. Secondary screening was done using fermented starch casein broth of the streptomycete to its stationary phase culture. The antibacterial agent was highly effective against all susceptible Gram negative bacteria except Proteus spp. Gram positive bacteria were relatively lesser sensitive. Pseudomonas aeruginosa was resistant to the agent. Antibacterial activity of aqueous fraction obtained from fermented broth of streptomycete culture was more effective than that of organic fraction of same extract. Thin layer chromatography revealed that the test compound was relatively nonpolar compared to the known antibiotics. Among the tested standard antibiotics, the chemical characteristic of the antibacterial agent was comparable to streptomycin. Key words: aminoglycoside; antibacterial agent; fermentation; secondary screening; thin layer chromatography DOI: 10.3126/njst.v9i0.3168 Nepal Journal of Science and Technology 9 (2008) 73-77